Especificidades institucionais / regionais no conceito de competitividade - Perosa, José Matheus Yalenti [UNESP]; Baiardi, Amilcar (Escola de Administração da Universidade Federal da Bahia, 1999)
This paper aims to discuss the concept of the competitiviness being taken I into consideration important institucional aspects. To do so a review of studies that discuss the concept strictly from an economic point of view and their limits in a context of transformation of the current world. Due to markets reorganization and to the new sources of competitiveness, the perspective of working with a wider concept that facilitates an articulation between economy and social organization opens up. Although of smaller operational power, that perspective offers alternative for analysis of the new competitiveness sources, as cultural, institutional and geographic aspects.

Este trabalho tem por objetivo discutir o conceito de competitividade levando-se em consideração aspectos institucionais relevantes. Para tanto, procedeu-se uma revisão de trabalhos que discutem o conceito de um ponto de vista estritamente econômico e seus limites num contexto de transformação do mundo atual. Face à reorganização de mercados e às novas fontes de vantagens competitivas, abre-se a perspectiva de se trabalhar com um conceito mais amplo que possibilite uma articulação entre economia e organização social. Embora de menor poder operacional, essa perspectiva oferece alternativa para análise de novas fontes da competitividade, tais como aspectos culturais, institucionais e geográficos.